1997
DOI: 10.1128/aem.63.10.3978-3984.1997
|View full text |Cite
|
Sign up to set email alerts
|

Single-site mutations in the conserved alternating-arginine region affect ionic channels formed by CryIAa, a Bacillus thuringiensis toxin

Abstract: The role of the third domain of CryIAa, a Bacillus thuringiensis insecticidal toxin, in toxin-induced membrane permeabilization in a receptor-free environment was investigated. Planar lipid bilayer experiments were conducted with the parental toxin and five proteins obtained by site-directed mutagenesis in block 4, an argininerich, highly conserved region of the protein. Four mutants were constructed by replacing the first arginine in position 21 by a lysine (R521K), a glutamine (R521Q), a histidine (R521H), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…A further effect worth considering is membrane potential. Schwartz et al (1997b) report the stimulating effect of a holding potential on insertion of toxin into artificial bilayers. In the present study, all cells were clamped to a holding potential of À40 mV and exposed to a protocol of variable potentials that may have enhanced pore formation.…”
Section: Discussionmentioning
confidence: 99%
“…A further effect worth considering is membrane potential. Schwartz et al (1997b) report the stimulating effect of a holding potential on insertion of toxin into artificial bilayers. In the present study, all cells were clamped to a holding potential of À40 mV and exposed to a protocol of variable potentials that may have enhanced pore formation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with site‐directed mutations in domain II loop residues suggested that the loop regions are important in the initial, reversible binding of BBMV and receptors, as well as in irreversible binding of BBMV (reviewed by Dean et al ., 1996). Domain III, a β‐sheet sandwich with a jelly roll topology, was originally suggested to play a role in toxin stability, but recent data strongly suggest that domain III is important in ion conductivity (Chen et al ., 1993; Schwartz et al ., 1997a), and receptor binding and specificity (Lee et al ., 1995b; 1999; deMaagd et al ., 1996; 1999; Burton et al ., 1999; Jenkins et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The comparatively simple structure of the Cry3A toxin , which is remarkably similar to Cry1Aa makes it a useful model for exploring the structure and function relationship between ligand and receptor. The three‐dimensional structure of the toxins consists of three functional domains: (i) a cluster of seven K‐helices predicted to be involved in membrane interaction (ii) three antiparallel L‐sheets involved in receptor binding ; and (iii) a L‐sandwich implicated in receptor binding and ion channel activity in related Cry toxins.…”
Section: Discussionmentioning
confidence: 99%